The Effect of Discipline and Motivation on Employee Performance of Perum Perhutani PHW IV Malang - Noveka Adetyani; Aniek Rumijati; Achmad Mohyi (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This research aims to find out and analyze the influence of discipline and motivation on employee performance. This type of research is survey research with a quantitative approach. The population in this study were all employees at Perum Perhutani PHW IV Malang, amounting to 33 people. The sample in this study amounted to 33 people selected using total sampling techniques. The data collection technique of this study was using a questionnaire. Technique data analysis was performed using multiple linear regression with two predictors, F test, T-test, and coefficient of determination. Based on test and analysis results, this study includes that, discipline has a significant effect on performance, motivation does not significantly influence performance, discipline and motivation have a simultaneous effect on performance, discipline has the more dominant influence on employee performance.